Implementasi Sistem Antrian Online Berbasis Aplikasi Mobile JKN pada Pelayanan Pasien Rawat Jalan Peserta BPJS Kesehatan di UPT Puskesmas Dadirejo (Progress, 2024)
In accordance with Law No. 40 of 2004 concerning the National Social Security System and Law No. 24 of 2011 concerning the Social Security Administering Body, the government provides basic guarantees for all Indonesian people, namely health insurance, work accident insurance, death and pension insurance. , and old age allowance. In the current development of information technology which leads to mobile application users, BPJS Health makes JKN-KIS (National Health Insurance-Healthy Indonesia Card) services easier. This application utilizes information technology which can be downloaded via the Mobile JKN application on Google Playstore or Apps Store. The aim of Mobile JKN is that people can enjoy services quickly. This research focuses on the person in charge and outpatient registration officers at the Dadirejo Health Center who provide outpatient registration services to BPJS Health participating patients as well as BPJS Health participating patients who have the Mobile JKN application who carry out outpatient registration at the Dadirejo Health Center. Respondents consisted of Dadirejo Community Health Center employees and outpatients. Data was collected through a direct interview process with respondents using an interview guide, direct observation of the activities of Dadirejo Health Center registration officers and patients as well as documentation studies of related documents. The results of the interviews show that the target has been achieved every month, but the level of effectiveness is still an average of 49% of the total number of visits. The obstacles faced by patients are due to the lack of supporting facilities and infrastructure at community health centers which are still inadequate.